Conceptual foundations of the theory of language in the philosophy of culture by A. F. Losev and E. Cassirer: a comparative analysis - Staskevich, Siarhei A. (Journal of the Belarusian State University. Philosophy and Psychology, 2025)
The methodological foundations of A. F. Losev’s and E. Cassirer’s linguistic theories are determined. It is proved that the linguistic theories of A. F. Losev and E. Cassirer play an important role in philosophical teachings. A. F. Losev’s and E. Cassirer’s linguistic theories play an important role in philosophical doctrines. The main similarities and differences of A. F. Losev’s and E. Cassirer’s approaches to language are revealed. The conclusion is made that for the emergence and functioning of a linguistic symbol a linguistic environment developed both in syntactic and semantic aspects is necessary.